Fallen - Hoblit, Gregory; Kazan, Nicholas, 1950-; Washington, Denzel, 1954-; Goodman, John, 1952-; Sutherland, Donald, 1935-; Davidtz, Embeth, 1966-; Gandolfini, James; Koteas, Elias, 1961-; Turner Pictures, Inc.; Atlas Entertainment (Firm); Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 1998)
Homicide detective John Hobbes witnesses the execution of serial killer Edgar Reese, but soon after the execution the killings start again, and they are very similar to Reese's style.
Originally released as motion picture in 1998.
Special features include: feature-length audio commentary by director Gregory Hoblit, screenwriter Nicholas Kazan and producer Charles Roven; interactive menus; production notes, theatrical trailer; scene access.
Executive producers, Nicholas Kazan, Elon Dershowitz, Robert Cavallo, Ted Kurdyla ; music composed and conducted by Tan Dun ; editor, Lawrence Jordan ; director of photography, Newton Thomas Sigel.
Denzel Washington, John Goodman, Donald Sutherland, Embeth Davidtz, James Gandolfini, Elias Koteas.
Rated R.
DVD; Dolby digital surround 5.1.
Keywords: Demonology -- Drama; Murderers -- Drama; Supernatural -- Drama; Paranormal drama; Feature films -- United States; Detective and mystery films; Drama; Horror films; Video recordings for the hearing impaired